AMBANG BATAS PARLEMEN (PERLIAMENTARY THRESHOLD) DAN ASAS DEMOKRASI - Strata, Tata; Hufron, Hufron; Setyadji, Sri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This research is a legal research (legal research). In this study, the approach used is the statutory approach, the case approach, and the conceptual approach. The legislative approach because the legal material used is the 1945 Constitution of the Republic of Indonesia, Law No. 10 of 2008 concerning General Elections for Members of the DPR, DPD, and DPRD, and Law no. 8 of 2012 concerning the Election of Members of DPR, DPD and DPRD. Case approach because the writer will refer to MKRI decisions related to the parliamentary threshold. The conceptual approach in this study because it refers to the views of scholars and legal doctrines. These three approaches, the author uses to give an exact position on how the principles of democracy should be used as guidelines related to the implementation of parliamentary training. The provisions of the parliamentary threshold in the Legislative Election Law are aimed at simplifying political parties. However, PT caused a serious consequence to thwart candidates who had fulfilled the BPP to sit in parliament. This condition is contrary to the principle of democracy in which one of its elements is the protection of minority representation. A near perfect representation will be realized when using a BPP benchmark and accompanied by a fractional threshold.